“A Head Start or a Pain in the Neck?”—Establishment and Evaluation of a Video-Based “Hands-On” Head and Neck Ultrasound Course - Lukas Pillong; Alessandro Bozzato; Dietmar Hecker; Victoria Bozzato; Bernhard Schick; Philipp Kulas (Diagnostics, 2022)
The COVID-19 pandemic has strongly highlighted the need for more digitalization in healthcare. Teaching ultrasound skills in online courses is a key challenge in this context. The aim of this study was to establish an online video-based head and neck ultrasound course with an evaluation of the quality, effectiveness, and feasibility of this teaching method compared to in-person teaching. Twenty-two medical students were taught head and neck ultrasound in two groups: one group in an in-person course and the other one in a video-based course. Learning success was analyzed using self-evaluation forms and external assessment by an experienced ultrasonographer. Comparing pre- and post-training self-evaluation, all participants showed statistically significant learning progress. In the external assessment, the overall scores in both groups did not differ significantly. The courses themselves were positively evaluated by all participants. Herein, we present the first feasibility study of a web-based head and neck-ultrasound course for medical students. The methodology provides the potential for future changes in telemedical education and sustainable improvements in telemedical teaching and global intra-clinical and interdisciplinary patient care.